Analysis of antibiotic use in diabetic ulcer patients at a private hospital in Surabaya - Fauna Herawati; Nadila Suleman; Rika Yulia; Heru Wijono (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Diabetic ulcer is one of the complications of diabetes mellitus in the form of chronic wounds due to neuropathy and peripheral arterial disease. Bacteria enter in a wound and cause a skin infection. Appropriate antibiotic therapy is needed to prevent antibiotic resistance. The purpose of this study was to evaluate the quantity profile of antibiotic use using the prescribed daily dose (PDD) and days of therapy (DOT) methods compared with the therapeutic guidelines (PPAB) in diabetic ulcer patients for the period January 2020 - June 2022 at a private hospital in Surabaya, Indonesia. This observational study with the retrospective data collection using medical records was analysed descriptively. The results showed that the total PDD value was 20.44 g/day. The highest antibiotic prescriptions were ceftriaxone (2.39 g/day) and metronidazole (1.46 g/day), respectively. The total days of therapy was 12.13 DOT; the DOT more than 4.00 were metronidazole (4.15 DOT) and ceftriaxone (4.09 DOT). This study reported a high PDD and DOT that will cause antibiotic resistance in the future.